Cosmetic materials
A decorative material with a resin base layer containing mica and talc stabilizes thermal expansion, addressing weight and dimensional issues, offering lightweight, high-strength, and reduced construction burden.
Patent Information
- Application Number
- JP2020181758
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-10-29
AI Technical Summary
Existing decorative materials made from wooden base materials face issues such as warping, insect damage, corrosion due to moisture absorption, and increased construction burden due to weight, while resin moldings with fibrous fillers have dimensional instability and economic challenges in widening.
A decorative material comprising a base layer made of resin containing 10-65 wt% mica and 5-60 wt% talc, with a high aspect ratio mica and controlled particle sizes, stabilizes thermal expansion and contraction, allowing for lightweight, high-strength, and dimensionally stable resin boards.
The solution provides a lightweight, high-strength decorative material with improved dimensional stability and reduced construction burden, maintaining foamability and surface smoothness.
Smart Images

Figure 0007600622000003 
Figure 0007600622000001 
Figure 0007600622000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a decorative material using a lightweight resin plate that has a resin cell structure, is strong, and places little strain on the construction process, and is used, for example, for architectural interior materials, flooring materials, fittings, and surface materials for home appliances. [Background technology]
[0002] 2. Description of the Related Art Conventionally, decorative sheets attached to wood substrates such as plywood and fiberboard have been widely used for applications such as architectural interior materials, flooring materials, fittings, and surface materials for home appliances. However, these decorative materials have problems with their physical properties, such as warping, insect damage, and corrosion, which are caused by the moisture absorption and release of the wood base material. In addition, because they are made of wood, the base material is heavy, making installation work a heavy burden. As a countermeasure to the above problems, many resin moldings containing a thermoplastic resin and a filler have been developed.
[0003] One of the molding methods is the Cerca process. The Cerca process is a molding method in which a special die is used to solidify the surface layer and form a low-foam layer while simultaneously forming a foam layer in the core (see paragraphs "0019" and "0028" and Figure 1 of Patent Document 1, and paragraphs "0030" and "0031" and Figure 1 of Patent Document 2). Resin molded products produced by the Cerca process have excellent workability for cutting, nailing, etc., and because a surface layer is formed, the surface is smooth and highly scratch-resistant. Also, because it is a foam, it is lightweight, requires little construction effort, and has high thermal insulation properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4206802 [Patent Document 2] Patent No. 3932883 Summary of the Invention [Problem to be solved by the invention]
[0005] However, since the above-mentioned Celca process is a profile extrusion molding process, the dimension in the width direction is shorter than the flow direction, and therefore different linear expansion properties are required in the flow direction and the width direction. For this reason, fibrous wood powder, which has a high effect of suppressing dimensional change in the flow direction, has often been used as a filler. However, it is difficult to make resin moldings containing fibrous fillers wide, which increases the workload during construction and poses economic challenges.
[0006] By adding scaly filler, it is possible to suppress linear expansion in both the machine and cross directions, and this effect can be further enhanced by increasing the filler mixing ratio. However, problems such as a decrease in base material strength and deterioration of foaming properties can occur, particularly under mixing conditions where the filler ratio is 50% or more.
[0007] On the other hand, narrow-width molded bodies are difficult to construct because of the heavy workload and economic problems involved, and therefore there is a demand for the development of wide-width molded bodies. With fibrous fillers such as wood powder, it is difficult to increase the width because of the difference in linear expansion between the flow direction and the width direction. One solution to the above problem is to incorporate a high amount of scaly filler with a high aspect ratio, which stabilizes the thermal expansion and contraction in the flow and width directions of the resin and makes it possible to mold widths from narrow to wide. However, this reduces the viscosity, which deteriorates foaming properties and surface smoothness.
[0008] Therefore, an object of the present invention is to provide a decorative material using a lightweight resin plate that is excellent in strength and imposes little strain during construction. That is, the decorative material according to the present invention uses a resin plate that has high dimensional stability without impairing foamability and strength. [Means for solving the problem]
[0009] A decorative material according to one aspect of the present invention is a decorative material comprising a base layer and a decorative sheet laminated on the base layer, the base layer having a celca structure made of a resin containing 10 to 65 wt% mica as a scale-like filler and 5 to 60 wt% talc, the total of the mica and the talc being 50 to 70 wt%, the mica having an aspect ratio of 10 or more, the particle size of the mica being 2 to 200 μm, and the particle size of the talc being 2 to 20 μm. The flexural elasticity of the base layer is 2000 to 9000 MPa (excluding cases where it is 4000 MPa or less). It is characterized in that: In addition, the decorative material according to one aspect of the present invention is characterized in that the flexural strength of the base layer is 30 MPa or more.
[0010] Books In one embodiment of the decorative material of the present invention, the base layer has a linear expansion coefficient in the flow direction of the resin during molding. and Linear expansion coefficient in the width direction both But 6.0×10 ―5 (1 / ℃) or less. The decorative material according to one aspect of the present invention is characterized in that the expansion ratio of the base layer is 1.4 to 4 times. Effect of the Invention
[0011] According to one aspect of the present invention, it is possible to provide a decorative material using a lightweight resin plate that has excellent strength and imposes little strain on the construction. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view of a decorative material according to a first embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (Embodiment 1) A first embodiment of the present invention will be described below with reference to the drawings. Here, the drawings are schematic, and the relationship between thickness and planar dimensions, the thickness ratio of each layer, etc. differ from the actual ones. Furthermore, the embodiments shown below are examples of configurations for embodying the technical idea of the present invention, and the technical idea of the present invention is not limited to the materials, shapes, structures, etc. of the components described below. The technical idea of the present invention can be modified in various ways within the technical scope defined by the claims.
[0014] (Decorative materials 10) In FIG. 1, 10 denotes a decorative material, and the decorative material 10 is used, for example, as a building interior material, a floor material, a fitting, a surface material for home appliances, and the like. As shown in FIG. 1, the decorative material 10 is roughly divided into the following two layers. The following layers will be described later. (1) Base material layer 20 (2) Decorative sheet 30
[0015] (Main features of cosmetic material 10) The main features of the decorative material 10 are as follows. (1) The decorative material 10 comprises a base layer 20 and a decorative sheet 30 laminated to the base layer 20 . (2) The base layer 20 is made of a resin containing 10 to 65 wt % of mica and 5 to 60 wt % of talc, and has a celca structure. If the mica content is less than 10 wt%, the strength will decrease, and if the talc content is less than 5 wt%, the foaming will become non-uniform due to gas escape.If the mica content exceeds 65 wt% or the talc content exceeds 60 wt%, the dispersion of the filler will be poor, and the strength will decrease, as well as the melt viscosity and foaming properties will deteriorate.
[0016] (3) The total amount of mica and talc is 50 to 70 wt %. If the total of mica and talc is less than 50%, the linear expansion coefficient of the resin will affect the resin, resulting in reduced dimensional stability. If it exceeds 70%, the filler will not disperse well, resulting in reduced strength, a reduced melt viscosity, and poor foaming properties.
[0017] (4) The mica has an aspect ratio of 10 or more. The mica preferably has an aspect ratio of 30 or more, and in order to suppress linear expansion and improve strength, it is preferable to use a filler with a high aspect ratio.
[0018] (5) The mica has a particle size of 2 to 200 μm, and the talc has a particle size of 2 to 20 μm. Mica is less dispersed in resin and strength decreases when it is less than 2 μm, and strength, homogeneity and flatness decrease when it exceeds 200 μm. Talc is less effective at stabilizing foaming and surface smoothness decreases when it is less than 2 μm or exceeds 20 μm. By virtue of the above-mentioned characteristics, the decorative material 10 can be provided with excellent strength, a small burden during application, and a lightweight base material layer 20 made of a resin board.
[0019] (Base material layer 20) The base material layer 20 contains a thermoplastic resin, mica, and talc, and has a Cerca structure. The thermoplastic resin may be, for example, polyolefin or vinyl chloride resin. The dimensions of the base layer 20 are, for example, a width of 100 mm or more and a length of 500 mm or more. As shown in FIG. 1, the base layer 20 is composed of the following layers: The following layers will be described later. (1) Foam layer 21 (2) Surface layer 22 (3) Adhesive layer 23
[0020] (Decorative sheet 30) The decorative sheet 30 is a sheet made of the same material as the base layer 20, such as polyolefin or vinyl chloride resin, on which a design, such as wood grain or an abstract pattern, is applied. As shown in FIG. 1, the decorative sheet 30 is composed of the following three layers. The following layers will be described later. (1) Printing layer 31 (2) Laminate 32 (3) Top Coat 33 The layers of the decorative sheet 30 are not limited to those (1) to (3) described above. Although not shown, the top coat 33 may be omitted, or the surface of the top coat 33 may be embossed.
[0021] (Foam layer 21) The foam layer 21 serves as a core material for the base layer 20, and contains a thermoplastic resin, mica, and talc. The foaming method may be, for example, chemical foaming, physical foaming, supercritical foaming, etc., and the foam structure may be independent foaming, continuous foaming, etc., with the foaming ratio being 1.4 to 4.0 times. If the foaming ratio is less than 1.4 times, the base material becomes heavy, which leads to an increased burden during construction, and if it exceeds 4.0 times, the strength of the base material decreases.
[0022] The expansion ratio varies depending on the intended use, but if the decorative material 10 is to be used, for example, as an indoor flooring material for a house or the like, the expansion ratio of the foam layer 21 is preferably 1.4 to 4.0 times, taking into consideration the balance of various aspects such as rigidity, surface strength, scratch resistance, indentation resistance, insulation, flexibility, feel, walking feel, flexibility, and workability.
[0023] By incorporating mica and talc into thermoplastic resin, the thermal expansion and contraction in the flow and width directions of the resin during molding is stabilized, making it possible to mold a wide range of widths from narrow to wide. In particular, with regard to talc, it prevents deterioration of foaming properties due to a decrease in viscosity that occurs when a Cerca structure is adopted.
[0024] (Surface layer 22) As shown in FIG. 1, the surface layer portions 22 are located above and below the foam layer 21, and improve the rigidity, surface strength, and the like of the surface of the foam layer 21. Although the surface layer 22 is shown in the drawing as forming a layer separate from the foam layer 21, in reality it is continuous with the surface of the foam layer 21 and there is no interface therebetween.
[0025] Moreover, the surface layer 22 is made of a thermoplastic resin having the same composition as the foamed layer 21, and is most preferably formed by the Cerca method, which is a molding method that allows continuous and stable molding in a single step. The surface layer 22 is non-foamed or low-foamed, whereas the foamed layer 21 is highly foamed, and the surface layer 22 and the foamed layer 21 have a continuous structure. Although the surface layer 22 is positioned above and below the foam layer 21, this is not limited thereto, and although not shown, it may be positioned only on one side, or may be formed so as to surround the surface of the foam layer 21.
[0026] (adhesive layer 23) The adhesive layer 23 is located between the upper surface of the surface layer 22 and the rear surface of the printed layer 31, and bonds the surface layer 22 and the printed layer 31 together. The adhesive used for the adhesive layer 23 may be of any type as long as it has the required adhesive strength.
[0027] (Print layer 31) The printed layer 31 is located on the surface of the adhesive layer 23 and is a sheet made of the same material as the base layer 20, such as polyolefin or polyvinyl chloride resin, with a design such as wood grain, stone grain, cloth grain, abstract pattern, etc.
[0028] (Laminate 32) Laminate 32 is The laminate 32 is located on the surface of the print layer 31 and serves to support the decorative sheet 30. The laminate 32 uses a sheet made of the same material as the base material layer 20, such as polyolefin or vinyl chloride resin.
[0029] (Topcoat 33) The top coat 33 is located on the surface of the laminate 32 and protects the surface to improve durability such as chemical resistance, scratch resistance, and dent resistance. Moreover, the surface of the top coat 33 may be embossed. By embossing the surface of the decorative material 10, it is possible to provide a configuration that gives a stronger three-dimensional feel to the touch. Although not shown, embossed patterns include, for example, duct grooves in wood grain boards, unevenness on the surface of a stone slab, textured cloth surface, matte finish, sand grain, hairline, and linear grooves.
[0030] (Material for decorative sheet 30) As for the material of the decorative sheet 30 having the printed layer 31, the same thermoplastic resin as that of the base layer 20 is used, and a design such as wood grain is printed on it, so there are no restrictions on the configuration of the decorative sheet 30 itself.
[0031] For example, a suitable selection can be made depending on the application from among single-layer decorative sheets in which a colored sheet has been printed, multi-layer decorative sheets in which a transparent sheet has been bonded to a printed colored sheet by dry lamination, extrusion lamination, heat lamination, etc., and back-printed single-layer decorative sheets in which a transparent sheet has been printed on the back side. In this case, if the decorative sheet has sufficient hiding power, stable reproduction of the design can be achieved, whereas, conversely, if the decorative sheet 30 has transparency, it becomes possible to express a design that makes use of the wood texture of the wooden base layer 20.
[0032] (Ink for decorative sheet 30) The ink used for printing the decorative sheet 30 may be appropriately selected from among soluble nitrocellulose, cellulose, vinyl chloride-vinyl acetate copolymer, polyvinyl butyral, polyurethane, acrylic, polyester, etc., either alone or in modified form, as a binder. These can be water-based, solvent-based, or emulsion types, and can be selected from either one-component types or two-component types using a hardener. Furthermore, the ink can be cured by exposure to ultraviolet light, electron beams, or the like. The most common method is to cure urethane-based inks with isocyanates.
[0033] (Additives) In addition to these binders, the ink contains the pigments, colorants such as dyes, extender pigments, solvents, and various additives that are normally contained in ink. Particularly commonly used pigments include condensed azo, insoluble azo, quinacridone, isoindolinone, anthraquinone, imidazolone, cobalt, phthalocyanine, carbon, titanium oxide, iron oxide, mica and other pearl pigments.
[0034] In addition, any of the decorative sheets may be coated with a primer coat for bonding to the base layer 20, a top coat for surface protection and gloss adjustment, or a vascular expression method such as embossing or gloss matte. The additives used in the printed layer 31 may be the same as those used in the base layer 20 .
[0035] (About thermoplastic resins) The thermoplastic resin used for the base layer 20 and the decorative sheet 30 can be appropriately selected from resins such as polyolefin, polystyrene, polycarbonate, polyester, polyamide, polyvinyl alcohol, acrylic, and polyvinyl chloride. However, in order to meet performance requirements such as the generation of dioxins during incineration and the leakage of environmental hormones during landfilling, as well as weather resistance, heat resistance, and resistance to chemicals and solvents as a component, it is desirable for the thermoplastic resin to be a polyolefin-based resin.
[0036] (About polyolefins) The "polyolefin" used herein can be appropriately selected from polyethylene, polypropylene, polybutene, polyisoprene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer, propylene-α-olefin copolymer, ethylene-ethyl acrylate copolymer, or any of these which have been acid-modified for the purpose of improving adhesion, ionomers, etc., and may be used alone or in combination of multiple types. However, in order to maintain the physical properties after recycling, it is better to have as good compatibility as possible. For example, in the case of polyethylene and polypropylene, when incompatible resins are mixed, such as in laminates, it is more desirable to blend a resin that makes them compatible, such as an ethylene-propylene copolymer.
[0037] In particular, in order to improve the adhesiveness, it is desirable to increase the compounding ratio of the acid-modified resin, impart polarity to the resin itself, and improve the adhesiveness to the filler. To improve foaming properties, it is desirable for the melt tension to be high, but in the Cerca process, good foaming is possible even with resins with low melt tension compared to sheet molding or normal irregular foam extrusion molding.
[0038] However, when gas escape, particularly when a high wood powder loading is used, is a concern, it is desirable to adjust the melt tension as necessary using known methods such as using a grade in which long chain branches have been introduced by electron beam crosslinking, controlling the molecular weight distribution, or blending in a fluorine-based additive that increases the melt tension.
[0039] (Additives) Additives that can be added as necessary include heat stabilizers, acid neutralizers, ultraviolet absorbers, light stabilizers, colorants such as pigments and dyes, fillers, antistatic agents, lubricants, nucleating agents, flame retardants, antiblocking agents, light scattering agents for making the resin semi-transparent, and gloss adjusters. Among these additives, examples of heat stabilizers include hindered phenols, sulfurs, and phosphorus-based additives; examples of acid neutralizers include metal stearates and hydrotalcites; examples of UV absorbers include benzotriazoles, benzoates, benzophenones, and triazines; examples of light stabilizers include hindered amines; examples of flame retardants include halogen-based flame retardants, phosphorus-based flame retardants, and chlorine-based flame retardants; examples of fillers include calcium carbonate, silica, titanium oxide, barium sulfate, zinc oxide, alumina, talc, mica, magnesium silicate, potassium titanate, magnesium sulfate, and hydroxide. Examples of additives that can be used in any combination include aluminum, magnesium hydroxide, iron oxide, carbon black, and metal powder. Examples of lubricants include hydrocarbon-based lubricants, fatty acids, higher alcohols, fatty acid amides, metal soaps, esters, and fluorine-based lubricants. Examples of nucleating agents include metal carboxylates, sorbitol, and metal phosphates. Examples of pigments include condensed azo, insoluble azo, quinacridone, isoindolinone, anthraquinone, imidazolone, cobalt, phthalocyanine, carbon, titanium oxide, iron oxide, and pearl pigments such as mica. These additives are generally used in any combination.
[0040] (Foaming method) As for the foaming method, any known method can be used. Generally, foaming agents can be classified into chemical foaming, which generates gas through thermal decomposition or chemical reaction, and physical foaming, which vaporizes a low-boiling liquid by applying heat. Chemical foaming agents include inorganic compounds such as sodium bicarbonate, ammonium carbonate, ammonium bicarbonate, ammonium nitrite, sodium borohydride, light metals, and azide compounds, while organic foaming agents include azo compounds, nitroso compounds, and hydrazide compounds, which can be used in any combination. In addition, physical foaming is mainly used for foaming at a high expansion ratio of more than 2 times, and carbon dioxide gas or aliphatic hydrocarbons are mainly used as the foaming agent. Furthermore, chemical foaming agents are often used in conjunction with physical foaming to regulate the cell shape of the foam.
[0041] (Similar thermoplastic resin) It is preferable that the thermoplastic resin does not undergo a significant change in physical properties when mixed with the thermoplastic resin of the same type, and that the mixed resin is recyclable. Specifically, examples of the resin include polyolefin-based, polystyrene-based, polycarbonate-based, polyester-based, polyamide-based, polyvinyl alcohol-based, acrylic-based, and polyvinyl chloride-based resins. For example, polyolefin-based resins include polyethylene, polypropylene, polybutene, polyisoprene, ethylene-propylene copolymer, ethylene-vinyl acetate copolymer, ethylene-α-olefin copolymer, propylene-α-olefin copolymer, ethylene-ethyl acrylate copolymer, and acid-modified versions of these for the purpose of improving adhesion, ionomers, etc., and the same or different resins selected from these can be used for the base layer 20 and the decorative sheet.
[0042] (Mixing method) There is no particular limit to the method by which the filler, talc, and thermoplastic resin can be mixed, but the most common methods are to mix them using a Banbury mixer or Henschel mixer and then pelletize them using a pelletizer, or to mix them and then pelletize them using a twin-screw extruder kneader. Furthermore, if the filler and talc have a high moisture content, it can cause foaming during molding, so it is desirable to reduce the moisture content to 8% or less using a dryer or hopper dryer before kneading. The filler and talc may be separately kneaded and pelletized, and then appropriately blended during molding. When the decorative material 10 is recycled, the crushed decorative material 10 is pelletized again after adding fillers, talc, thermoplastic resins, various additives, etc. as necessary. In this case, the method is not particularly limited. Furthermore, the filler and the resin may be kneaded at the same time as forming the base layer 20 .
[0043] (Selkie structure) The Cerca structure is a structure obtained by the Cerca method or an equivalent structure. The Cerca method is a foam extrusion molding method in which an extrusion die having outlet dimensions approximately the same as or slightly smaller than the inlet dimensions of a cooling sizing die is used, and a foamable resin composition is extruded from the extrusion die with the outlet of the extrusion die and the inlet of the cooling sizing die being brought into close contact with each other, thereby introducing the foamable resin composition into the cooling sizing die in a state in which foaming has hardly progressed, and foaming occurs mainly inside the cooling sizing die.
[0044] The Celca structure is not limited to structures formed by the above-mentioned methods, and is characterized in that at least a portion of the surface layer 22 is non-foamed or low-foamed, the foam layer 21 is highly foamed, the non-foamed or low-foamed surface layer 22 and the foam layer 21 are made of thermoplastic resins of the same composition, and the foam layer 21 and the surface layer 22 have a continuous structure.
[0045] (Method of manufacturing decorative material 10) A method for producing the decorative material 10 having the above-mentioned configuration will now be described. A base material layer 20 and a decorative sheet 30 are separately manufactured, and as shown in FIG. 1, the front surface of adhesive layer 23 of base material layer 20 is adhered to the rear surface of printed layer 31 of decorative sheet 30 to manufacture decorative material 10.
[0046] (Actions and Effects of the First Embodiment) The functions and effects of the first embodiment are as follows. (1) One aspect of this embodiment 1 is a decorative material 10 consisting of a base layer 20 and a decorative sheet 30 laminated to the base layer 20, in which the base layer 20 has a ceramic structure consisting of a resin containing 10 to 65 wt% mica and 5 to 60 wt% talc, the total of the mica and talc being 50 to 70 wt%, the mica having an aspect ratio of 10 or more, the mica having a particle size of 2 to 200 μm, and the talc having a particle size of 2 to 20 μm. According to the first embodiment, it is possible to provide a decorative material using a lightweight resin plate that has excellent strength and imposes little strain during application.
[0047] (2) In one aspect of the first embodiment, the flexural strength of the base layer 20 is 30 MPa or more. If the bending strength of the base layer 20 is less than 30 MPa, the strength of the base material decreases. (3) In one aspect of the first embodiment, the flexural modulus of the base layer 20 is 2000 to 9000 MPa. If the flexural modulus is less than 2000 MPa, the rigidity and surface hardness are insufficient, and scratch resistance and indentation resistance are deteriorated.If the flexural modulus exceeds 9000 MPa, the substrate becomes hard, causing a poor walking feel and a decrease in flexural strength.
[0048] (4) In one aspect of the first embodiment, the linear expansion coefficient in the resin flow direction during molding in the base layer 20 is and Linear expansion coefficient in the width direction both But 6.0×10 -5 (1 / ℃) or less. these At least one of the linear expansion coefficients, i.e., one in the flow direction, one in the width direction, or both in the flow direction and the width direction, is 6.0×10 -5 If this value is exceeded, dimensional stability will be compromised and the risks of warping, bumping, and grain defects will increase.
[0049] (5) In the first embodiment, the expansion ratio of the base layer 20 is 1.4 to 4 times. If the foaming ratio is less than 1.4 times, the base material becomes heavy, which leads to an increased burden during construction, and if it exceeds 4 times, the strength of the base material decreases. The foaming ratio varies depending on the intended use, but if the decorative material 10 is to be used, for example, as an indoor flooring material for a house or the like, the foaming ratio of the foamed layer 21 is preferably 1.4 to 4.0 times, taking into consideration the balance of various aspects such as rigidity, surface strength, scratch resistance, indentation resistance, insulation, flexibility, feel, walking feel, flexibility, and workability. EXAMPLES
[0050] Hereinafter, the present embodiment 1 will be described more specifically with reference to Examples 1 to 12 and Comparative Examples 1 to 11. However, the present invention is not limited to the following Examples 1 to 12.
[0051] Example 1 The main conditions of Example 1 are as shown in Table 1 below. In addition, in Table 1 below, in addition to Example 1, the conditions for Examples 2 to 12 and Comparative Examples 1 to 11 are also shown. [Table 1]
[0052] In Example 1, 29 parts by weight of polypropylene, 60 parts by weight of filler, and 1 part by weight of maleic acid-modified polypropylene were mixed and pelletized in a twin-screw kneader as shown in Table 1. The pellets were expanded 2.6 times by chemical foaming using a sodium bicarbonate-citric acid foaming agent, and formed into a rectangular parallelepiped shape with a thickness of 5 mm by the Celca process to produce the base layer of the decorative material of Example 1.
[0053] The conditions for Example 1, as shown in Table 1 above, are as follows: (1) Aspect ratio of mica used in the base layer: 80 (2) Ratio (wt%) of the total weight of mica and talc to the total weight of the base layer: 60 wt% (3) Mica blend ratio (wt%): 30wt% (4) Talc blend ratio (wt%): 30wt% (5) Mica particle size (μm): 60 μm (6) Talc particle size (μm): 9 μm
[0054] Example 2 In Example 2, the aspect ratio of the mica in Example 1 was reduced from "80" to "10," and a base layer of Example 2 was produced in the same manner as in Example 1.
[0055] (Examples 3 to 8) As shown in Table 1 above, in Examples 3 to 8, in addition to the aspect ratio of the mica in Example 1, the compounding ratio of the mica to the talc was changed. In Example 3, the aspect ratio of the mica was changed to “80”, the total blend weight ratio of the mica and the talc was changed to “50”, the blend ratio of the mica was changed to “25”, and the blend ratio of the talc was changed to “25”. The base material layer of Example 3 was produced in the same manner as Example 1.
[0056] Example 4 In Example 4, the base layer of Example 4 was produced in the same manner as Example 1, except that the total blend weight ratio of mica and talc was changed to "70", the blend ratio of mica to "35", and the blend ratio of talc to "35".
[0057] Example 5 In Example 5, the base layer of Example 5 was produced in the same manner as Example 1, except that the total blend weight ratio of mica and talc was changed to "70", the blend ratio of mica to "65", and the blend ratio of talc to "5".
[0058] Example 6 In Example 6, the base layer of Example 6 was produced in the same manner as Example 1, except that the total blend weight ratio of mica and talc was changed to "60", the blend ratio of mica to "10", and the blend ratio of talc to "50".
[0059] Example 7 In Example 7, the base layer of Example 7 was produced in the same manner as Example 1, except that the total blend weight ratio of mica and talc was changed to "70", the blend ratio of mica to "10", and the blend ratio of talc to "60".
[0060] Example 8 In Example 8, the base layer of Example 8 was produced in the same manner as in Example 1, except that the total blend weight ratio of mica and talc was changed to "60", the blend ratio of mica to "55", and the blend ratio of talc to "5".
[0061] (Examples 9 to 12) In Examples 9 to 12, as shown in Table 1 above, in addition to the aspect ratio of the mica and the blending ratio of the mica and talc in Example 1, the particle sizes of the mica and talc were changed. In Example 9, the aspect ratio of the mica was changed to “85”, the total weight ratio of the mica and talc was changed to “60”, the blending ratio of the mica was changed to “30”, the blending ratio of the talc was changed to “30”, the particle size of the mica was changed to “200”, and the particle size of the talc was changed to “9”, and the base layer of Example 9 was produced in the same manner as in Example 1.
[0062] Example 10 In Example 10, the aspect ratio of the mica was changed to “12”, the total weight ratio of the mica and talc was changed to “60”, the blending ratio of the mica was changed to “30”, the blending ratio of the talc was changed to “30”, the particle size of the mica was changed to “2”, and the particle size of the talc was changed to “9”. The base layer of Example 10 was produced in the same manner as in Example 1.
[0063] Example 11 In Example 11, the aspect ratio of the mica was changed to "80", the total blend weight ratio of the mica and talc was changed to "60", the blend ratio of the mica was changed to "30", the blend ratio of the talc was changed to "30", the particle size of the mica was changed to "60", and the particle size of the talc was changed to "20". The base layer of Example 11 was produced in the same manner as in Example 1.
[0064] Example 12 In Example 12, the aspect ratio of the mica was changed to “80”, the total blend weight ratio of the mica and the talc was changed to “60”, the blend ratio of the mica was changed to “30”, the blend ratio of the talc was changed to “30”, the particle size of the mica was changed to “60”, and the particle size of the talc was changed to “2”, and the base layer of Example 12 was produced in the same manner as in Example 1.
[0065] Comparative Example 1 In Comparative Example 1, the aspect ratio of the mica in Example 1 was reduced from "80" to "9," and a base layer of Comparative Example 1 was produced in the same manner as in Example 1.
[0066] (Comparative Examples 2 to 7) In Comparative Examples 2 to 7, as shown in Table 1 above, the blending ratio of mica and talc in Example 1 was changed. In Comparative Example 2, the base material layer was produced in the same manner as in Example 1, except that the total blend weight ratio of mica and talc was changed to "40", the blend ratio of mica to "20", and the blend ratio of talc to "20".
[0067] Comparative Example 3 In Comparative Example 3, the base material layer was produced in the same manner as in Comparative Example 3, except that the total blend weight ratio of mica and talc was changed to "80", the blend ratio of mica to "40", and the blend ratio of talc to "40".
[0068] Comparative Example 4 In Comparative Example 4, the base material layer was produced in the same manner as in Comparative Example 2, except that the total blend weight ratio of mica and talc was changed to "70", the blend ratio of mica to "66", and the blend ratio of talc to "4".
[0069] Comparative Example 5 In Comparative Example 5, the total blend weight ratio of mica and talc was changed to “60”, the blend ratio of mica to “9”, and the blend ratio of talc to “51”, and the base material layer of Comparative Example 5 was produced in the same manner as in Comparative Example 2.
[0070] Comparative Example 6 In Comparative Example 6, the total blend weight ratio of mica and talc was changed to “70”, the blend ratio of mica to “9”, and the blend ratio of talc to “61”, and the base material layer of Comparative Example 6 was produced in the same manner as in Comparative Example 2.
[0071] Comparative Example 7 In Comparative Example 7, the total blend weight ratio of mica and talc was changed to "60", the blend ratio of mica to "56", and the blend ratio of talc to "4", and the base material layer of Comparative Example 7 was produced in the same manner as in Comparative Example 2.
[0072] (Comparative Examples 8 to 11) In Comparative Examples 8 to 11, as shown in Table 1 above, in addition to the aspect ratio of the mica in Example 1, the particle sizes of the mica and talc were changed. In Comparative Example 8, the aspect ratio of the mica was changed to "100", the particle size of the mica was changed to "120", and the particle size of the talc was changed to "9", and the base layer of Comparative Example 8 was produced in the same manner as in Example 1.
[0073] Comparative Example 9 In Comparative Example 9, the aspect ratio of the mica was changed to "10", the particle size of the mica was changed to "1", and the particle size of the talc was changed to "9", and the base layer of Comparative Example 9 was produced in the same manner as in Example 1.
[0074] Comparative Example 10 In Comparative Example 10, the particle size of the mica was changed to "60" and the particle size of the talc was changed to "21", and the base layer of Comparative Example 10 was produced in the same manner as in Example 1.
[0075] Comparative Example 11 In Comparative Example 11, the particle size of the mica was changed to "60" and the particle size of the talc was changed to "1", and the base layer of Comparative Example 11 was produced in the same manner as in Example 1.
[0076] (Evaluation items) The evaluation items consist of the following five items. The following evaluation items will be described later. (1) Bending strength of base layer (Mpa) (2) Bending elasticity of the base layer (Mpa) (3) Linear expansion coefficient in the flow direction (MD) of the resin during molding of the base layer (MD × 10 -5 )[1 / ℃] (4) As in (3) above, the linear expansion coefficient in the transverse direction (TD) (TD × 10 -5 )[1 / ℃] (5) Foaming ratio of base layer
[0077] (Bending strength of base layer) The bending strength of the base material layer was evaluated on a two-level scale, with 30 MPa or more being rated as "◯" (pass) and anything else, ie, less than 30 MPa being rated as "×" (fail).
[0078] (Bending elasticity of base layer) The bending elasticity of the base material layer was evaluated on a two-level scale, with a range of 2000 to 9000 MPa being rated as "◯" and other values, ie, values less than 2000 MPa or exceeding 9000 MPa being rated as "×" and failing.
[0079] (Linear expansion coefficient in machine direction (MD)) The linear expansion coefficient was evaluated for the above-mentioned Examples 1 to 10 and Comparative Examples 1 to 9. The linear expansion coefficient was evaluated by calculating the linear expansion coefficient in the temperature range of 10°C to 70°C using a thermomechanical analyzer TMA (product name). The linear expansion coefficient in the machine direction (MD) is evaluated in two stages, and is 6.0×10 -5 (1 / ℃) or less is considered to be "○" and passed, and the rest, i.e., 6.0×10 -5 (1 / ℃) was marked as "×" and was a failure.
[0080] (Linear expansion coefficient in transverse direction (TD)) The linear expansion coefficient in the transverse direction (TD) was evaluated in two stages and was 6.0×10 -5 (1 / ℃) or less is considered to be "○" and passed, and the rest, i.e., 6.0×10 -5 (1 / ℃) was marked as "×" and was a failure.
[0081] (Expansion ratio of base layer) The expansion ratio of the base material layer was rated as "◯" when it was within the range of 1.4 to 4 times, and was rated as "×" and unsuccessful when it was otherwise, that is, less than 1.4 times or more than 4 times.
[0082] (Evaluation Results) The results are shown in Table 2. [Table 2]
[0083] As shown in Table 2 above, Examples 1 to 12 passed all five items. In contrast to this, all of Comparative Examples 1 to 11 failed.
[0084] (About bending strength) Among Comparative Examples 1 to 11, the five samples (Comparative Example 3, and Comparative Examples 8 to 11) failed the first bending strength test. In Comparative Example 3, the bending strength was too low at "15 MPa" compared to less than 30 MPa, and it was rejected with an "X" mark. Similarly, the remaining Comparative Examples 8 to 11 were also too low at "24 MPa," "25 MPa," "29 MPa," and "22 MPa," respectively. In Comparative Example 1, the total blend weight ratio of mica and talc was "80 wt %", which is presumably too high.
[0085] For this reason, from the viewpoint of bending strength, the total blend weight ratio of mica and talc needs to be less than "80 wt %." In Comparative Example 8, the particle size of the mica was 210 μm ", which is too large, and Comparative Example 9 is "1 μm " So we can surmise that it was too small. Therefore, from the viewpoint of bending strength, the particle size of mica is set to "210 μm " and "1 μm " It is necessary to go beyond that.
[0086] In Comparative Example 10, the particle size of the talc was "21 μm ", which is too large, and Comparative Example 11 is "1 μm " So we can surmise that it was too small. Therefore, from the viewpoint of bending strength, the particle size of talc is set to "21 μm " and "1 μm " It is necessary to go beyond that.
[0087] (About bending elasticity) Among Comparative Examples 1 to 11, Comparative Example 3 was the only one that failed the second bending modulus. Comparative Example 3 has a bending modulus of "9210 MPa" which is too high while the bending modulus is within the range of 2000 to 9000 MPa, and is therefore marked as "x" and rejected.
[0088] In Comparative Example 3, the total blend weight ratio of mica and talc was "80 wt %", which is presumably too high. For this reason, from the viewpoint of bending elasticity, the total blend weight ratio of mica and talc must be less than "80 wt %."
[0089] (Linear expansion coefficient in machine direction (MD)) Among Comparative Examples 1 to 11, the three comparative examples 1, 2, and 5 failed the third linear expansion coefficient in the machine direction (MD). In Comparative Example 1, the linear expansion coefficient in the machine direction (MD) is 6.0 × 10 -5 (1 / ℃), while the average temperature is below 60.5 (1 / ℃), which is too high, so it is marked as "X" and rejected. Similarly, the remaining Comparative Examples 2 and 5 are also too high, at 63.1 (1 / ℃) and 60.3 (1 / ℃), respectively.
[0090] It can be assumed that in Comparative Example 1, the aspect ratio of the mica was "9", which was too low. For this reason, from the viewpoint of the linear expansion coefficient in the machine direction (MD), it is necessary that the aspect ratio of the mica exceeds "9." In Comparative Example 2, the total blend weight ratio of mica and talc was "40 wt %", which is presumably too low.
[0091] For this reason, from the viewpoint of the linear expansion coefficient in the machine direction (MD), the combined weight ratio of mica and talc needs to exceed "40 wt%." In Comparative Example 5, the blending ratio of mica was "9", which is presumably too low. For this reason, from the viewpoint of the linear expansion coefficient in the machine direction (MD), the blending ratio of mica needs to exceed "9."
[0092] (Linear expansion coefficient in the transverse direction (TD)) Among Comparative Examples 1 to 11, the four comparative examples 1, 2, 5, and 6 failed the fourth linear expansion coefficient in the transverse direction (TD). In Comparative Example 1, the linear expansion coefficient in the transverse direction (TD) is 6.0 × 10 -5 (1 / ℃), while the average temperature is below 70.3 (1 / ℃), the average temperature is too high at 68.3 (1 / ℃), so it is marked as "X" and rejected. Similarly, the remaining Comparative Examples 2, 5, and 6 are also too high at 70.3 (1 / ℃), 62.7 (1 / ℃), and 60.8 (1 / ℃), respectively.
[0093] For Comparative Examples 1, 2 and 5, the linear expansion coefficient in the machine direction (MD) is the same as that in the comparative examples. It can be assumed that in Comparative Example 6, the blending ratio of mica was "9", which was too low, and the blending ratio of talc was "61", which was too high. For this reason, from the viewpoint of the linear expansion coefficient in the machine direction (MD), the blending ratio of mica needs to exceed "9wt%" and the blending ratio of talc needs to be less than "61wt%."
[0094] (About foaming ratio) Among Comparative Examples 1 to 11, the four comparative examples 4, 7, 8, and 10 failed the fifth bending modulus. In Comparative Example 4, the expansion ratio is too low at "1.1" while it is within the range of 1.4 to 4 times, so it is rejected with an "X" rating. Similarly, the remaining Comparative Examples 7, 8, and 10 are also too low at "1.3", "1.3", and "1.2", respectively. It can be assumed that in Comparative Example 4, the blending ratio of mica was "9", which was too low. For this reason, from the viewpoint of expansion ratio, the blending ratio of mica needs to exceed "9wt%."
[0095] It can be assumed that in Comparative Example 7, the blending ratio of talc was too low at "4t%." For this reason, from the viewpoint of the expansion ratio, it is necessary that the talc content exceeds "4 wt%."
[0096] In Comparative Example 8, the particle size of the mica was 210 μm " So we can assume that it was too big. Therefore, from the viewpoint of expansion ratio, the particle size of mica is "210 μm " or less.
[0097] In Comparative Example 10, the particle size of the talc was "21 μm " So we can assume that it was too big. Therefore, from the viewpoint of expansion ratio, the particle size of talc is "21 μm " or less. [Explanation of symbols]
[0098] 10 Cosmetic materials 20 Base material layer 21 Foam layer 22 Surface layer 23 Adhesive layer 30 Decorative Sheet 31 Printing layer 32 Lamination 33 Top Coat
Claims
1. A decorative material comprising a base layer and a decorative sheet laminated on the base layer, The substrate layer is The ceramic structure is made of a resin containing 10 to 65 wt % mica and 5 to 60 wt % talc, The total amount of the mica and the talc is 50 to 70 wt %, The mica has an aspect ratio of 10 or more; The particle size of the mica is 2 to 200 μm, and the particle size of the talc is 2 to 20 μm, A decorative material characterized in that the flexural modulus of the base layer is 2000 to 9000 MPa (excluding cases where it is 4000 MPa or less).
2. 2. The decorative material according to claim 1, wherein the flexural strength of the base layer is 30 MPa or more.
3. In the base material layer, both the linear expansion coefficient in the resin flow direction and the linear expansion coefficient in the width direction during molding are 6.0×10 ―5 3. The decorative material according to claim 1, wherein the thermal expansion coefficient is 1 / ° C. or less.
4. 4. The decorative material according to claim 1, wherein the expansion ratio of the base layer is 1.4 to 4 times.
Citation Information
Patent Citations
Member for molding and inner part
JP2000117908A
Plastic board using spent plastic as raw material and its manufacturing method
JP2003155825A
Molded foam and method for producing the same
JP2008081648A
Floor material, floor structure and extraction method of some floor material
JP2017101499A
Polyphenylene sulfide resin composition
JP2017179041A
